Incidence, Complications, and Factors Associated with Out-of-Hospital First Attempt Intubation Failure in Adult Patients: A Secondary Analysis of the CURASMUR Trial Data. (4th March 2022) - Nicol, Thomas; Gil-Jardiné, Cédric; Jabre, Patricia; Adnet, Frederic; Ecollan, Patrick; Guihard, Bertrand; Ferdynus, Cyril; Combes, Xavier
Abstract: Objectives: The objectives of this study were to evaluate first attempt intubation failure rate, its associated factors, and its related complications in out-of-hospital emergency setting, when emergency physicians perform standardized airway management using rapid sequence intubation in adult patients. Material and methods : The present study was a substudy of the Succinylcholine versus Rocuronium for out-of-hospital Emergency Intubation (CURASMUR) Trial, which compared Succinylcholine and Rocuronium used for Rapid sequence intubation. First attempt Intubation failure rate and early intubation related complications were recorded. We used multivariable logistic regression analysis to determine first intubation failure associated factors. Results : A total of 1230 patients were included with mean age of 55.9 +/- 19 years. First attempt intubation failure was recorded in 285 (23.2%) patients. The occurrence of a first attempt intubation failure was independently associated with history of ear, nose, and throat neoplasia (OR 2.20, CI 95% 1.06–4.60). Early intubation related complications were more frequent in case of first attempt intubation failure: 80 of 285 (28.4%) in patients with first attempt intubation failure and 185 of 945 (19.6%) in patients with successful first attempt intubation [OR 1.44; CI 95%, 1.11–1.87]. Conclusion : Based on a large multicenter study on out-of-hospital tracheal intubation of adult patients, we found that first attempt intubation failure rate was high and that history of ear, nose, and throat (ENT) neoplasia was an independent associated factor. Failure in first intubation attempt was associated with significantly more intubation related complications.